Advances of Accurate Quantification Methods in Food Analysis - Li, Xianjiang; Weng, Rui (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Food safety is a matter of great significance for the global population. Therefore, researchers have been developing and validating analytical methods to extract, separate and quantitate a variety of hazardous and nutritional analytes in various food commodities. Due to the complexity of food components, a suitable pretreatment method is required to eliminate matrix effects and lower the detection limit. Afterward, chromatography and mass spectrometry are powerful tools in the guarantee of food safety and quality. This book is the reprint of a Special Issue of Separations, "Advances of Accurate Quantification Methods in Food Analysis", and provides an overview of recent trends in food analytical methods. Both novel sample pretreatment and detection techniques are covered, with the aim of accurate quantification. This Special Issue received nine contributions that covered the latest analytical methods, and focused on pesticides, mycotoxin, antibiotics, metal ions, organic selenium and anthocyanins.